Perlindungan Hukum Terhadap Pekerja Harian Lepas Pada Perusahaan Yang Bergerak Dalam Bidang Logistik - Aura Syahranni; Dita Cahyani Sudirman; Halimah Citra Negoro; Nabila Alya Husna; Nadila Khairunnisa; Qristiana Qristiana; Salsabilla Putri Alaika; Sri Juwita Putri; Mustika Mega Wijaya (Universitas Katolik Widya Karya Malang, 2023)
This increase is very important for a country, especially for a developing country like Indonesia. Along with continuous improvement, progress is characterized as a conscious effort by the state. One of the things that is very important in the progress of a nation is its workers, that in the rapid progress of a country, it is the workers who start. That departing from this, the government is an important part in winning progress in the business sector as well as for the national development program which must be endeavored to open up as many jobs as possible from various layers of trade that are able to balance the increase in quality and increase in security for the workforce which can become a must. Whereas Article 27 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that